2015
DOI: 10.1128/mbio.02300-14
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of a Foodborne Norovirus Outbreak Strain with Nonthermal Atmospheric Pressure Plasma

Abstract: Human norovirus (NoV) is the most frequent cause of epidemic nonbacterial acute gastroenteritis worldwide. We investigated the impact of nonthermal or cold atmospheric pressure plasma (CAPP) on the inactivation of a clinical human outbreak NoV, GII.4. Three different dilutions of a NoV-positive stool sample were prepared and subsequently treated with CAPP for various lengths of time, up to 15 min. NoV viral loads were quantified by quantitative real-time reverse transcription PCR (RT-qPCR). Increased CAPP trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 24 publications
2
48
0
Order By: Relevance
“…It has been reported that several factors can influence the inhibitory effects, such as microbial species, exposure type, injected gas type, and the number of cell layers in the sample . The plasma emits antiviral and antimicrobial materials, such as photons, electrons, positive and negative ions, free radicals, neutral atoms, UV photons, as well as reactive oxygen and reactive nitrogen species, with enough energy to affect the foodborne pathogens (Wan et al, 2009;Ahlfeld et al, 2015). During the exposure to the plasma, these particles have a sterilization effect by directly being in contact with the surface.…”
Section: Inactivation Effects Of App Jets On Mnv-1 and Hav On The Frementioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that several factors can influence the inhibitory effects, such as microbial species, exposure type, injected gas type, and the number of cell layers in the sample . The plasma emits antiviral and antimicrobial materials, such as photons, electrons, positive and negative ions, free radicals, neutral atoms, UV photons, as well as reactive oxygen and reactive nitrogen species, with enough energy to affect the foodborne pathogens (Wan et al, 2009;Ahlfeld et al, 2015). During the exposure to the plasma, these particles have a sterilization effect by directly being in contact with the surface.…”
Section: Inactivation Effects Of App Jets On Mnv-1 and Hav On The Frementioning
confidence: 99%
“…Plasma consists of photons, electrons, positive and negative ions, free radicals, neutral atoms, UV photons, reactive oxygen (ozone, atomic oxygen and singlet oxygen) and reactive nitrogen species (NO radicals,NO 2 ,NO 3 , N 2 O 3 , N 2 O 4 and ONOO¯) (Ahlfeld et al, 2015;Gweon et al, 2010;Wan, Coventry, Swiergon, Sanguansri, & Versteeg, 2009). Various active species and UV photons were inactivating the virus particles, bacteria, fungi and yeast by destroying the genetic material (Ahlfeld et al, 2015;Fridman et al, 2007;Moisan et al, 2001Moisan et al, , 2002. In addition, the beginning of the exposure to the APP, these elements generate a synergistic effect (Ahlfeld et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These species, initially generated in the gas phase, are further delivered by the plasma to the biological substrate 5 . RONS interact with substrates and thus define the antimicrobial, anticancer and antiviral effects of LTP [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%